Factors Influencing Mental Health of Medical Workers During the COVID-19 Outbreak - Yan Zhang; Simiao Xie; Pu Wang; Pu Wang; Pu Wang; Guixiang Wang; Li Zhang; Xiaochen Cao; Wenzhi Wu; Yueran Bian; Fei Huang; Na Luo; et al. (Frontiers Media S.A., 2020)
Background: Since the outbreak of COVID-19, physical and psychological harm has been spreading across the global population alongside the spread of the virus. Currently, the novel coronavirus has spread to most countries in the world, and its impact on the public is also increasing. As a high-risk group in direct contact with the virus, medical workers should be monitored, and their mental health deserves extensive attention. The aim of this study was to explore the mental health of medical workers facing the novel coronavirus and the main factors affecting it.Methods: The present cross-sectional study including 2,100 eligible individuals from 1,050 hospitals in China was conducted through the network platform powered by www.wjx.cn, a platform providing functions equivalent to Amazon Mechanical Turk. We used a self-designed questionnaire to collect demographic information and data on mental states, including gender, age (years), educational level, job rank, body and mind reaction, cognition of risk, and the judgment of the epidemic situation. Independent samples t-tests and one-way (ANOVA) analysis were carried out to compare the differences in the mental reactions according to the demographic and psychological states of the participants.Results: There were 502 males (23.9%) and 1,598 females (76.1%). The participants reported feeling calm (39.1%), tense (63.0%), scared (31.4%), angry (18.8%), sad (49.0%), afraid (34.7%), optimistic (5.1%), impressed (65.0%), and confident (31.1%) during the epidemic. At the same time, the psychological stress responses of medical staff were significantly different according to the levels of exposure in their environments, duration and personal experience.Conclusions: Prolonged exposure to the virus and intense work are detrimental to the mental health of medical care personnel. It is necessary to adjust work conditions and intensity according to workers' mental state flexibly and systematically.